2021
DOI: 10.3389/fimmu.2021.618196
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Surface Antigen Suppresses the Activation of Nuclear Factor Kappa B Pathway via Interaction With the TAK1-TAB2 Complex

Abstract: Chronic hepatitis B is a major health problem worldwide, with more than 250 million chronic carriers. Hepatitis B virus interferes with the host innate immune system so as to evade elimination via almost all of its constituent proteins; nevertheless, the function of HBsAg with respect to immune escape remains unclear. This study aimed to determine the role HBsAg plays in assisting HBV to escape from immune responses. We found that HBsAg suppressed the activation of the nuclear factor kappa B (NF-кB) pathway, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Besides, a TAB2-deficient mouse resulted in embryonic lethality due to liver degeneration and apoptosis [58]. These results indicate that TAB2 plays a crucial role in the liver [59], and fish TAB2 might play a similar role in the function of the liver [60].…”
Section: Discussionmentioning
confidence: 82%
“…Besides, a TAB2-deficient mouse resulted in embryonic lethality due to liver degeneration and apoptosis [58]. These results indicate that TAB2 plays a crucial role in the liver [59], and fish TAB2 might play a similar role in the function of the liver [60].…”
Section: Discussionmentioning
confidence: 82%
“…In the human myeloma B-cell line RPMI 8226, HBsAg dysregulated TLR9 malfunction by inhibiting transcription factor CREB activation [ 89 ]. Deng et al also found that HBsAg interfered the NF-κB signaling by binding to the TAK1 and TAB2 complex, leading to an attenuated immunological response [ 90 ]. In addition, a reduction of activated NK cells was found in the liver of HBsAg-expressing mice, indicating that HBV could affect immune cell activation by regulating immunosuppressive signal pathways and cytokines [ 91 ].…”
Section: Mechanism Of Immunosuppression In Hepatitis B Virus Infectionmentioning
confidence: 99%
“…Indeed, HBV components have been reported to interrupt the intracellular signaling pathways of TLRs. HBsAg inhibits IRF7 expression and nuclear translocation in pDCs (34) and also interferes with the NF-kB pathway by interacting with the TAK1-TAB2 complex (35). Moreover, HBeAg has been reported to disrupt homotypic TIR : TIR interactions and thus suppress TIR-mediated activation of the NF-kB and IFN-a promoters (36).…”
Section: Impaired Expression and Function Of Tlrs In Hbv Infectionmentioning
confidence: 99%